Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Building an Acceptable Use Policy - Tanweer, Rabia; Wyss, Natalie (EdTech Hub, 2023)
Acceptable use policies (AUPs) aim to define how digital and technological tools and services (both devices and ICT services) should be used in or by education systems and actors. These policies address the rights, privileges, responsibilities, and ramifications associated with the use of technology in education spaces and for educational purposes. In doing so, AUPs attempt to promote good practice and responsible, safe use of the internet and digital technologies. This brief uses global examples of AUP policies and guidance on the development of AUPs to outline best practices and key considerations for the development of AUPs. Keywords: EdTech usage; acceptable use policy; tablets; laptops; desktop computers; EdTech hardware; EdTech software. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2020)
This paper analyses a range of literature reviews to identify characteristics of effective teacher education, including focusing on practical subject pedagogy; incorporating peer support and; creating a coherent policy environment.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _forthcoming; _zenodoETH:submitted; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Characteristics of effective teacher education in low- and middle-income countries: an annotated bibliography (HDR10C) - McBurnie, Chris; Allier-Gagneur, Zoe; Haßler, Björn (EdTech Hub, 2020)
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

EdTech Initiatives Focused on Classrooms and Teachers: A Curated List for Rwanda - Chuang, Rachel; Koomar, Saalim (EdTech Hub, 2020)
This document was produced in response to a request from the FCDO Rwanda team for a curated list of EdTech initiatives related to the following focus areas: 1. Classroom software 2. Teacher education 3. School administration.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted